PERKEMBANGAN SOSIAL ANAK USIA DINI SEBAGAI BIBIT UNTUK MASA DEPAN BANGSA - Mayar, Farida (AT-TALIM, 2013)
Children social development is determined by the childâs individual, the roles of parents, social environment, and Kindegarten.Â  There is a strong relationship between the ability to socialize and the happiness in the childhood.Â  Â The childâs ability to adapt to the environment and the acceptance of environment as well as positive experiences in their social activities serve as crucial factor to reach fun and successful life in the future.Â  Social development is actually a maturity achievement in the social relationship.Â  It can also refer to learning process to adapt to the social norm, moral and tradition:Â  Diffusing into an interrelationship unit to communicate and cooperate.Â  Social development in a family is also influenced by several factors such as status of the family, unity of family, attitudes, andÂ  parentsâ habit.Â CopyrightÂ Â©Â 2013 by Al-TalimÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v20i3.43